Prognostic influences and prediction model construction for traumatic cervical spinal cord injury - Kang, Xin; Zhang, Xiao-bo; Gao, Xi-dan; Gao, Zi-lin; Xu, Zheng-wei; Zhang, Yingang (Frontiers in Neurology, 2026)
Study designRetrospective analysis of prognostic factors in traumatic cervical spinal cord injury (TCSCI) patients.ObjectiveExplore a novel approach for the prognosis assessment of TCSCI.MethodsA retrospective analysis of clinical data was conducted on patients who underwent operation at Xi’an Honghui Hospital between March 2016 and May 2023. The study included sex, age, hypertension, diabetes mellitus (DM), damage range, ossification of the posterior longitudinal ligament (OPLL), cervical spinal canal stenosis grading (CSCS), surgical timing, and postoperative complications (deep vein thrombosis, pulmonary complications, pressure ulcers, and urinary tract infections). A prognostic model was established by these differential factors and evaluating the sensitivity and specificity for predicting paralysis occurrence.ResultsParalysis was found to be 4.009 times more likely in patients with DM compared to those without (95% CI: 1.250–12.863, p = 0.020). Patients with diffuse damage had a 7.912 times higher likelihood of developing paralysis than those without diffuse damage (95% CI: 3.466–18.063, p < 0.001). Patients with CSCS grade III had an 8.862 times higher likelihood of developing paralysis compared to those with grades 0, I, or II (95% CI: 3.280–23.946, p < 0.001). The probability of paralysis with ≥2 postoperative complications was 4.625 times greater (95% CI, 1.107–19.323, p = 0.036) than without complications. The probability of paralysis in patients with surgical times >3 days was 3.132 times greater (95% CI, 1.325–7.407, p = 0.036) than within 3 days (95% CI, 1.325–7.407, p = 0.009). The CSCS had the greatest effect on the prognosis of patients with paralysis, followed by the damage range. Sex, age, hypertension, and OPLL were not associated with prognosis (p > 0.05).ConclusionThe prognosis of TCSCI is influenced by factors including DM, damage range, CSCS, surgical timing, and the number of postoperative complications. A clinical prognostic model was developed based on these prognostic factors, demonstrating a strong predictive capability for paralysis.